Perbaikan Faktor Daya Pada Sistem Kelistrikan di PT. Pertamina Hulu Rokan Dengan Simulasi Aliran Beban Menggunakan Etap - Ridal, Yani (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Electrical energy needs a very significant increase every year and according to the supply voltage to provide enough quality electricity supply. The increase in energy demand is also followed by the demand for reactive power due to increased inductive loads. PT. Pertamina Hulu Rokan is one of the users of quite large inductive loads, because almost at every point of the oil drilling location there are inductive loads installed including transformers and induction motors. In this writing, the author tries to briefly describe the use of bank capacitors used at PT. Pertamina Hulu Rokan. From the data and research results that have been carried out, it can be concluded that, with the addition of bank capacitors to the electrical system at PT.Pertamina Hulu Rokan it can help compensate for the lack of reactive power in the electrical system which is currently being used at PT.Pertamina Hulu Rokan